RETRACTED: Evaluating the growing importance of IT in the management of transport logistics and supply chain - Khurramov Azizbek; Khurramova Madina Mansur qizi; Kholmirzaev Mansur; Minavvarov Javoxir; Ergashev Giyosjon; Djalilova Malika; Esankulov Abdullo Eshpulatovich (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001